A Evaluasi Program Bina Iman Anak Menggunakan Model Cipp (Contect, Input, Process, Product) - Damanik, Randi Arnaldo; Lumbanbatu, Johannes Sohirimon (Jurnal Kala Nea, 2025)
Children’s faith formation plays a crucial role in the Church’s mission to instill Christian values from an early age, especially amid digital challenges and limited family support. This study aims to evaluate the Children's Faith Formation program at stasi Santo Thomas Rasul Purba Saribu using the CIPP model (Context, Input, Process, Product). A qualitative approach was employed with data gathered through observation, interviews, and documentation. The results show that contextually, the program aligns with the Church’s vision and addresses the children’s spiritual needs. In terms of input, the facilitators demonstrated strong dedication despite limited formal catechetical training. The process of activities was carried out regularly, employing various methods that actively engaged the children. From the product aspect, there was an observable improvement in faith knowledge and participation in church life. This study concludes that the CIPP model is effective for evaluating children's faith formation programs comprehensively and can serve as a strategic foundation for developing more impactful and contextually relevant programs.